How best to engage users of forensic services in research: literature review and recommendations - Völlm, Birgit; Foster, Sheena; Bates, Peter; Huband, Nick (Taylor & Francis, 2017)
Guidance on service user involvement is available to help researchers working with people with mental health problems, but there is currently no comprehensive guidance relating to forensic settings where additional issues arise. This rapid review aims to summarise the currently available information on how best to engage users of forensic mental health services in the research process, and to make appropriate recommendations. Medline and five other databases were searched to May 2016 using relevant keywords and Medical Subject Headings, supplemented by a general Internet search. Eleven peer-reviewed journal papers and 12 reports or web-based documents were identified, the majority containing information derived using a qualitative methodology. Five areas of particular relevance to forensic settings were identified: power relations & vulnerability issues (including ethical treatment; informed consent; attitudes of staff and other service users; support), practical difficulties (including ‘consultation fatigue’; tokenistic inclusion; tensions over security and risk management; access; payment; co-authoring); confidentiality and transparency; language and communication and training issues. Recommendations on engaging service users in forensic mental health research are presented.